Superconductivity in strongly correlated electronic systems - Plakida, N. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2009)
A microscopic theory of superconducting pairing within the Hubbard model is discussed. A Dyson equation for the matrix thermodynamic Green function in the Nambu representation for Hubbard operators is derived by applying the Mori-type projection technique for the equation of motion method. The self-energy is calculated in the noncrossing approximation for electron scattering on spin and charge fluctuations induced by kinematic interaction for Hubbard operators. It is shown that perconducting pairing in strongly correlated electronic systems is determined by antiferromagnetic exchange caused by interband hopping and spin fluctuations due to hole motion in one subband.